Visitors expectation and experience in recreation at Tasek Bera / Sri Rahayu Mohd Sa'ad, Azman A. Rahman and Zakaria Hashim - Mohd Sa'ad, Sri Rahayu; A. Rahman, Azman; Hashim, Zakaria (Research Management Institute (RMI), 2010)
Ecotourism is one of the approach that have high potential towards the sustainable concept which integrates the economic return and the most important in balancing natural resources and provide a priority to local communities and local cultural in its planning and implementation consideration. This research is needed to improve park management knowledge in offering good quality experience in recreation to ecotourism visitors. Tasek Bera located at Pahang, has been chosen in this study and this research involving 32 respondents. Variable in visitors expectation and experience in recreation including difficulties in movement in ecotourism area, social interaction and sense of remoteness. Finding found that the main attraction Tasek Bera is the nature beauty and also the recreation activities. Visitors expect difficulties in movement from the main road to Tasek Bera and the movement in all attraction areas in Tasek Bera, but it is not in actual experience. Visitor expectations are higher compared to visitor experience in remoteness factor. This place gives them opportunity to solitude and closed to nature. Unfortunately, forest in Tasek Bera not enough challenging for some visitor so high confidence level is not needed as other ecotourism areas. Visitors also expect to convergent with others tourist during they recreation activity. Since majority of respondents come from 'generalist' visitors so the infrastructure development in Tasek Bera still can be accepted from their view.